Atomic force microscopy visualization of hard segment alignment in stretched polyurethane nanofibers prepared by electrospinning - Hiroaki Sakamoto (Science and Technology of Advanced Materials, 2014)
Molecular-level orientation within nanofibers has been attracting attention as a tool for controlling and designing highly functional nanofibers. In this study, we used atomic force microscopy to visualize the phase separation between soft and hard segments on a polyurethane (PU) nanofiber surface prepared by electrospinning. Furthermore, the stretched nanofibers prepared with a high-speed rotating collector were found to have a different phase distribution in the phase-separated structure, with the hard segment domains aligned to the fiber axis. In contrast, unstretched PU nanofibers prepared without rotation were observed to have nonuniformly distributed segments. These results indicate that the application of an intense elongation force along the nanofiber axis with a rotating mandrel collector changed the distribution of segment alignments.